Evaluation of the remineralization potential of different bioactive glass varnishes on white spot lesions: an in vitro study - M. M. Sleem; El-Sayed Gad Eid; A. M. Abdelghany; D. S. Farahat (BMC Oral Health)
Abstract Background White spot lesions represent the first clinical sign of dental caries and can be reversed using various remineralizing agents. This study aimed to synthesize different bioactive glass varnishes and assess their remineralizing effects on white spot lesions compared to fluoride varnish and a synthesized nanosilver fluoride varnish. Methods Seventy-two extracted human teeth were used. The teeth were divided into seven groups (n = 10): Group A (Artificial saliva, negative control), Group B (Fluoride varnish), Group C (Bioactive glass varnish), Group D (Fluoride-containing bioactive glass varnish), Group E (Nanosilver-containing bioactive glass varnish), Group F (Nanosilver fluoride varnish), and Group G (Nanosilver varnish). The different varnishes were synthesized and then characterized via transmission electron microscopy and UV-vis spectroscopy. Artificial caries were induced in the specimens by immersion in a demineralizing solution for 4 days. Each specimen was analyzed at baseline and in the demineralized state and after two weeks of varnish application by Energy Dispersive X-ray analysis and Vickers micro-hardness tester. One representative specimen from each group, one specimen at baseline, and one demineralized specimen were examined using scanning electron microscopy. Statistical analysis was conducted using one-way analysis of variance (ANOVA) and repeated measures ANOVA followed by Tukey’s post hoc test. Results The nanosilver-containing bioactive glass group (E) presented the highest mineral gain percentage, followed by fluoride-containing bioactive glass (D) and nanosilver fluoride (F) groups, with insignificant differences between groups D and F. Groups D, E, and F showed the highest hardness recovery percentages, with insignificant differences among them. Scanning electron microscopy revealed the development of new crystals in these groups. Conclusions Bioactive glass varnish is a promising remineralizing agent with efficacy comparable to fluoride varnish. The fluoride-containing and nanosilver-containing bioactive glass varnishes had a higher remineralizing potential compared to the fluoride and bioactive glass varnishes and nearly the same remineralizing effect of the nanosilver fluoride varnish.